ESTIMATION OF METHIONINE AND LYSINE IN PROTEIN BY THIN-LAYER CHROMATOGRAPHY - H.Mohammadiha; P. Mostafavi (Tehran University of Medical Sciences, 1983)
A thin-layer chromatography method has been developed and evaluated for the separation and determination of lysine and methonine in a mixture of amino acids obtained from acid or enzyme hydrolysis of protein. The solvent systems were (a) ethanol-ether, (b) phenol-water, (c) ethyl methyl ketone-pyridine-distilled water-glacial acetic acid. Procedures in all the three stages were in the same dimension. Results of casein analysis by this method showed ± 15% fluctuations when compared with standard amino acid analyzer.